GluN1 and GluN2A NMDA Receptor Subunits Increase in the Hippocampus during Memory Consolidation in the Rat - Cercato, Magali C.; Vázquez, Cecilia A.; Kornisiuk, Edgar; Aguirre, Alejandra I.; Colettis, Natalia; Snitcofsky, Marina; Jerusalinsky, Diana A.; Baez, María V. (Frontiers in Behavioral Neuroscience, 2017)
It is widely accepted that NMDA receptors (NMDAR) are required for learning and memory formation, and for synaptic plasticity induction. We have previously shown that hippocampal GluN1 and GluN2A NMDAR subunits significantly increased following habituation of rats to an open field (OF), while GluN2B remained unchanged. Similar results were obtained after CA1-LTP induction in rat hippocampal slices. Other studies have also shown NMDAR up regulation at earlier and later time points after LTP induction or learning acquisition. In this work, we have studied NMDAR subunits levels in the hippocampus and prefrontal cortex (PFC) after OF habituation and after object recognition (OR), to find out whether rising of NMDAR subunits is a general and structure-specific feature during memory formation. In 1, 2 and 3 months old rats there was an increase in hippocampal GluN1 and GluN2A, but not in GluN2B levels 70 minutes after OF habituation. This rise overlaps with early phase of memory consolidation, suggesting a putative relationship between them. The increases fell down to control levels 90 minutes after training. Similar results were obtained in the hippocampus of adult rats 70 minutes after OR training, without changes in PFC. Following OF test or OR discrimination phase, NMDAR subunits remained unchanged. Hence, rising of hippocampal GluN1 and GluN2A appears to be a general feature after novel ‘spatial/ discrimination’ memory acquisition. To start investigating the dynamics and possible mechanisms of these changes, we have studied hippocampal neuron cultures stimulated by KCl to induce plasticity. GluN1 and GluN2A increased both in dendrites and neuronal bodies, reaching a maximum 75 minutes later and returning to control levels at 90 minutes. Translation and/or transcription and mobilization differentially contribute to this rise in subunits in bodies and dendrites. Our results showed that the NMDAR subunits increase follows a similar time course both in vitro and in vivo. These changes happen in the hippocampus where a spatial representation of the environment is being formed making possible STM and LTM; appear to be structure-specific; are preserved along life; and could be related to synaptic tagging and/or to memory consolidation of new spatial/discrimination information.